Pelatihan Perpajakan dan Pemanfaatan Teknologi Komputer untuk Mendukung UMKM pada Era Digital di MA Nurul Ilmi Bategede Jepara - Abror, A. Faiq; Purwati; Prabawati, Chintya (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Banyuwangi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in national economic growth; however, many MSME actors still face limitations in understanding tax obligations and utilizing computer technology. This Community Service Program (PkM) aimed to improve tax literacy and digital technology skills among students of MA Nurul Ilmi Bategede, Jepara. The methods used included lectures, practice sessions, and evaluations through pre-tests and post-tests. The training results showed a significant improvement in understanding: before the training, 91.5% of students scored below the Minimum Mastery Criteria (MMC), while after the training, this number decreased to 25.3%. Student responses indicated that 100% considered the training relevant to their needs, and the majority stated that the material was easy to understand. Thus, this activity proved effective in enhancing students’ knowledge and skills related to taxation and the use of computer technology to support MSMEs in the digital era